Urbanization homogenizes the interactions of plant-frugivore bird networks - Schneiberg, Israel; Boscolo, Danilo; Devoto, Mariano; Marcilio-Silva, Vinicius; Dalmaso, Cilmar Antônio; Ribeiro, John Wesley [UNESP]; Ribeiro, Milton Cezar [UNESP]; de Camargo Guaraldo, André; Niebuhr, Bernardo Brandão [UNESP]; Varassin, Isabela Galarda (My University, 2020)
Anthropogenic activities are the main cause of habitat loss and fragmentation, which directly affects biodiversity. Disruption in landscape connectivity among populations may affect complex interactions between species and ecosystem functions, such as pollination and seed dispersal, and ultimately result in secondary extinctions. Urbanization, one of the most intense forms of landscapes changes, has been reported to negatively affect bird and plant diversity. Still, little is known about the effects of urban landscapes on interaction networks. We investigated the relationship between urban landscape structure and plant-frugivore networks at different spatial scales. Coupling interaction data from urban areas and a model selection approach, we evaluated which landscape factors best explained the variation in urban networks properties. Our results indicate that urbanization decreases bird richness, mainly through the loss of habitat specialist species, which results in networks being composed mainly of birds well adapted to urban dwelling. We found that interaction evenness, a measure of homogeneity of interaction distribution between species, increases with urbanization. This is due to the strong dominance that generalist birds had in network composition because they foraged on all available fruits, including exotic plants. The ensuing homogenization of interactions can reduce the resilience of networks and affect the efficiency of ecosystems functions. Thus, urbanization plans should consider the proportion and distribution of green areas within cities, coupling human and ecosystem wellbeing.
Keywords: Landscape ecology; Mutualistic network; Urban environmental